Determination of the Spatial Resolution of Radar Images in Remote Sensing of the Earth - S. N. Gusev; S. V. Zhuravlev; A. V. Popov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The analysis of the current state and prospects of space-based radar surveillance tools is important for determining their functions in global aerospace information systems, which aim to monitor air and space, as well as the Earth's surface. Radar surveillance information is used for the purposes of economic analysis, environmental monitoring, mineral search, emergency monitoring, detection and recognition of specified object s at sea and on land, as well as for ensuring national security. In this regard, it is of relevance to develop methods for preliminary assessment of the resolution capacity of novel high-precision onboard radar systems installed on a spacecraft, considering their main technical characteristics, the parameters of the spacecraft movement and the influence of the atmosphere. A priori estimation of spatial resolution values requires a method for calculating the corresponding indicators meeting the required quality of the synthesized radio holograms.Aim. To derive mathematical dependencies and logical rules allowing a priori estimation of the spatial resolution of radar images obtained by the onboard equipment of a radar complex.Materials and methods. Analytical methods were used to determine the resolution error of onboard radar systems with a synthesized aperture in the lateral (azimuthal) direction and range, as well as the theory of radar signal processing.Results. A comparison of the experimental and analytical data on the resolution capacity of an actual radar system confirmed the validity on the proposed method. The developed methodology was used to determine the procedure of calculating the error when estimating the resolution capacity in terms of azimuth and range. Conclusion. The proposed method can be used for both designing novel radar systems and comparing existing radar complexes, depending on the resolution requirements.